Differences and similarities in local ecological knowledge about rays among fishers, residents, and tourists - Freitas, Ricardo Franco; Machado, Lucas Peixoto; de Freitas, Renato Hajenius Aché; Hanazaki, Natalia (Ethnobiology and Conservation, 2021)
Ray species have been globally threatened due to high fishing pressure and habitat loss. In southern Brazil fisheries, despite many ray species are protected by law and usually non-targeted species, they are captured along with commercially important species. However, as in all of Brazil, there is evidence that rays are consumed, that is, there is a demand for meat from these animals, which intensifies the risk of extinction. Marine ethnobiology is an alternative approach to better understand these organisms, considering the traditional empirical knowledge of fishers and local communities. Our objective is to evaluate the knowledge of local residents, fishers, and tourists about the occurrence, distribution, reproduction, and feeding of ray species and also ray consumption among them. We hypothesized that fishers and locals have a deeper ecological knowledge about rays than tourists, and fishers should know more than residents. Individual interviews were conducted for three consecutive days at Armação beach, Florianópolis, Brazil. We asked people about ray biology and ecology based on questionnaires. Each respondent was categorized into three groups: fishers, locals, and tourists; and ranked according to an index of ecological knowledge of rays. The fishers had greater knowledge about rays, followed by residents and tourists. Additionally, fishers and locals consume rays, even the trade is prohibited locally, evidencing the need for legal enforcement. The fishers’ knowledge may be essential for management of fish stocks, contributing to sustainable fishing and species conservation. In contrast, the tourists' lack of knowledge evidences the need to raise awareness of these animals.